Linguistic Landscape Study At Tourism Place In Medan - Nasution, Mutia Nursyafitri (Universitas Muhammadiyah Sumatera Utara, 2021)
This research deals with a study of linguistic landscape specifically language usedin the sign at tourism places of Medan.It mainly aimed to investigate on three issues as follows: firstly, to investigate what languages are realized on linguistic land scape, secondly, to investigate the types of sign categories on linguistic landscape and thirdly is reason the realization of linguistic landscape at tourismplaces in Medan. The research is applied descriptive qualitative method. The dataof this research is the written text displayed on signs that was taken through photography and taking note. There are 82 signs collected that were analyzed through applying Miles and Huberman the oryin which data reduction, data display, and conclusion drawing/verification are significantly implemented. The results of the data analysis showed that the languages found in the linguistic landscape at Tourism Places in Medan are Bahasa Indonesia (monolingual sign),Bahasa Indonesia-English Language(bilingualsign),English language(Monolingual sing), and English language-Bahasa Indonesia (bilingual sign). It also showed that the types of Sign categories at Tourism Places in Medan wererealized as direction signs, advertising signs, warning notices and prohibitions,buildingnames,informativesign,sloganssign,andgraffitisign.